2021
DOI: 10.3389/fnins.2021.731602
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbial Load and Immune Activation in a Drosophila Model of Human Tauopathy

Abstract: Tau is a microtubule-associated protein that stabilizes the neuronal cytoskeleton. In the family of neurodegenerative diseases known as tauopathies, including Alzheimer’s disease (AD), frontotemporal dementia (FTD), and chronic traumatic encephalopathy (CTE), abnormal tau aggregation destabilizes microtubule structure, contributing to a cascade of cellular processes leading to neuronal cell death. The gut microbiome has increasingly become a target of neurodegenerative disease research since gut microbiome imb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Interestingly, these bacterial species display similar health-promoting proprieties in Drosophila and mammals (Erkosar et al, 2013). For instance study of microbiota in transgenic fly models for NDs have revealed correlation between shift in microbial population and aging (Kitani-Morii et al, 2021;Neophytou and Pitsouli, 2022;Schretter, 2020;von Frieling et al, 2020) or the onset of NDs similar to that observed in humans (Mertsalmi et al, 2020;Rydbom et al, 2021).…”
Section: Figurementioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, these bacterial species display similar health-promoting proprieties in Drosophila and mammals (Erkosar et al, 2013). For instance study of microbiota in transgenic fly models for NDs have revealed correlation between shift in microbial population and aging (Kitani-Morii et al, 2021;Neophytou and Pitsouli, 2022;Schretter, 2020;von Frieling et al, 2020) or the onset of NDs similar to that observed in humans (Mertsalmi et al, 2020;Rydbom et al, 2021).…”
Section: Figurementioning
confidence: 94%
“…Neurological diseases, such as NDs are co-morbid with gastrointestinal alterations (Vandvik et al, 2004;Sampson and Sarkis, 2015). It has indeed been reported that in both mouse and Drosophila models of human PD, the neurodegenerative pathologies in the brain have been observed in concurrence with commensal dysbiosis in the gut (Erny et al, 2015;Challis et al, 2020;Peterson, 2020;Kitani-Morii et al, 2021;Rydbom et al, 2021).…”
Section: Microbiota Composition and Ndsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, microbiome studies on Drosophila flies carrying the transgenic mutant human FTDP-17-associated tau showed reduced gut motility and subsequently increased gut bacterial load in aged tau transgenic compared to control flies [ 121 ].…”
Section: The Gut Microbiome and Amyotrophic Lateral Sclerosis/frontot...mentioning
confidence: 99%